Perspectives of Teachers and Parents of Children with Autism Spectrum Disorder on the Importance of the Parent-Teacher Relationship - Fitzgibbon, Kate (Marino Institute of Education, 2020)
‘One in every 65 students or 1.5% of the school’s population has a diagnosis of ASD which is approximately 14,000 students’ (NCSE, 2016, p. 32). This statistic highlights the number of students reported on the autism spectrum in Ireland. This study explores perspectives of teachers and parents of children with ASD on the importance of the parent-teacher relationship. A qualitative, constructivist approach using one-to-one semi-structured interviews was the chosen methodology to conduct this study as it was considered the most appropriate means to gain insights into the participant's perceptions, experiences, and attitudes. The study’s main research questions focus on exploring teachers’ and parents’ perceptions on the importance the parent-teacher relationship and on factors that support and hinder the development of this relationship. The research participants included three parents of primary school children with ASD, three special education teachers working in a special class and three teachers working in a mainstream primary school. The main findings of this study indicate that there is a need for regular, informal communication between the parent and teacher of a child with ASD to support the child’s needs and the parent-teacher relations. Parent-teacher relationships are reported in the study as supporting the child’s academic and behavioural outcomes, alleviating parental stress, encouraging parental involvement in the child’s education, acting as a bridge between home and school, particularly for non-verbal children. It emerged from the findings that having multiple communication platforms and a positive school ethos supported the development of the parent-teacher relationship. This study highlights barriers to the development of this relationship while identifying the factors that can encourage the establishment of a parent-teacher relationship. Recommendations are made for encouraging the development of the parent teacher relationship and areas for future research are identified.
Keywords: Research Subject Categories